The strand transfer oligonucleotide inhibitors of HIV-integrase - Snásel, Jan; Rosenberg, Ivan; Paces, Ondrej; Pichová, Iva (Journal of enzyme inhibition and medicinal chemistry, 2009)
Retroviral integrase participates in two catalytic reactions, which require interactions with the two ends of the viral DNA in the 3'processing reaction, and with a targeted host DNA in the strand transfer reaction. The 3'-hydroxyl group of 2'-deoxyadenosine resulting from the specific removing of GT dinucleotide from the viral DNA in the processing reaction provides the attachment site for the host DNA in a transesterification reaction. We synthesized oligonucleotides (ONs) of various lengths that mimic the processed HIV-1 U5 terminus of the proviral long terminal repeat (LTR) and are ended by 2'-deoxyadenosine containing a 3'-O-phosphonomethyl group. The duplex stability of phosphonomethyl ONs was increased by covalent linkage of the modified strand with its complementary strand by a triethylene glycol loop (TEG). Modified ONs containing up to 10 bases inhibited in vitro the strand transfer reaction catalyzed by HIV-1 integrase at nanomolar concentrations.
Keywords: HIV Integrase Inhibitors; HIV-integrasa; HIV Long Terminal Repeat; HIV Integrase; konformace nukleové kyseliny; Nucleic Acid Conformation; Oligonucleotides; inhibitory HIV-integrasy; oligonukleotidy; molekulární mimikry; kyseliny fosforu; Molecular Mimicry; HIV - dlouhá koncová repetice; Phosphorus Acids